Amelioration of cyclophosphamide-induced DNA damage, oxidative stress, and hepato- and neurotoxicity by Piper longum extract in rats: The role of γH2AX and 8-OHdG - Yadav, Vaishali; Krishnan, Anuja; Zahiruddin, Sultan; Ahmad, Sayeed; Vohora, Divya (Frontiers in Pharmacology, 2023)
Background: Identification of genoprotectants is a promising strategy for improving human health. Piper longum has drawn scientific attention because of its diverse biological effects and traditional utilization. The present study aimed to evaluate the genome stabilizing potential of Piper longum extract against cyclophosphamide-induced genotoxicity. Methods: We adopted a funnel screening with a three tier-evaluation approach where Piper longum was investigated in acellular medium, peripheral blood lymphocytes and rodent model. The genoprotective action of Piper longum extract was initially performed with plasmid pBluescriptSK(-) DNA. Further, extract and various fractions were screened against cyclophosphamide-induced genotoxicity using cytokinesis-block micronucleus assay and chromosomal aberrations assay in human peripheral blood lymphocytes. The genome stabilizing action of extract and potent (hexane) fraction was further confirmed in vivo in Wistar albino rats by evaluating mammalian erythrocyte micronucleus test, DNA fragmentation, oxidative stress markers, 8-hydroxy-2-dexyguanosine (8-OHdG), γH2AX and histopathological lesions in liver and hippocampus. Additionally, acute and sub-acute toxicity studies were carried out following OECD guidelines in rats. Further, extract was quantified and characterized by HPTLC, UPLC-MS & GC-MS. Results: Piper longum ethanol extract revealed protection of plasmid pBluescriptSK(-) DNA against H2O2 induced strand breaks. In human lymphocytes, extract and hexane fraction showed reduction in micronucleus formation (p<0.001) and chromosomal aberrations (p<0.01) against cyclophosphamide. Further, extract and fraction treatment, when administered at 200mg/kg for 28 days in Wistar rats, restored cyclophosphamide-induced genomic instability by reducing micronucleus formation and DNA fragmentation, restoring redox homeostasis, decreasing 8-OHdG, a marker of oxidative DNA damage, and reducing γH2AX, a DNA double strand break marker, as well as, preserving liver and hippocampus against histopathological lesions. Extract and fraction revealed no signs of systemic toxicity at the employed doses. Piperine and piperlongumine are the major alkaloids quantified, along with the presences of flavonoids in ethanol extract, while presences of fatty acids and terpenoids in the hexane fraction of Piper longum. Conclusion: Our investigation confirms the genoprotective action of Piper longum by reducing cyclophosphamide-associated cytogenotoxicity, oxidative stress, hepato-, and neurotoxicity, oxidative DNA damage and DNA double strand breaks. The findings are significant in terms of reducing genotoxic impact of chemotherapy receiving patients requiring further attention.